Non-Steroidal Anti-Inflammatory Drug Hypersensitivity in Children - Alves, C (2017)
There are rather few publications about hypersensitivity reactions to non-steroidal anti-inflammatory drugs (NSAID) in the paediatric age. In this study, we aimed to assess the frequency of confirmed NSAID hypersensitivity in children with a previous reported reaction to NSAID in order to investigate the role of the drug provocation test (DPT) in the diagnostic workup and to explore the factors associated with confirmed NSAID hypersensitivity.